Innovating Wellness: Police Personnel Perspectives on Strategies to Improve Access and Engagement - Smith, Hayden (Criminal justice and behavior, 2025)
Police personnel face numerous occupational hazards that can severely compromise their physical and mental health. Despite decades of scholarship on the subject, little is known about how best to deliver wellness knowledge and interventions to this workgroup. To address this research void, semistructured interviews were conducted with (n = 17) sworn and (n = 9) civilian police personnel from a large metropolitan law enforcement agency in the Mid-Atlantic United States. Participants offered insight regarding the stigmatization associated with help-seeking behaviors and best practices for treatment delivery, while also providing their opinions on eight innovative health strategies. Respondents voiced support for wellness apps, written toolkits, and group games, while therapeutic support groups were valued if led by credible messengers. Comic books, virtual reality, and card games generated considerable curiosity, whereas video clips were viewed negatively. Findings are used to strategize effective ways of delivering wellness programs to police personnel.